Packaged Software Implementation Requirements Engineering by Small Software Enterprises: An Ethnographic Study - Jebreen, Issam (Auckland University of Technology, 2014)
This thesis investigates the practices of requirements engineering (RE) for packaged software implementation, as enacted by small packaged software vendors (SPSVs). Throughout the thesis, a focus on the actions carried out by SPSVs analysts during RE is maintained, rather than a focus on the actions of client companies. The thesis confirms the assertions literatures finding that most contemporary RE practices are unsuitable for SPSVs. The research investigated the means by which SPSVs can adopt, follow and adapt the best possible RE practices for packaged software implementation (PSI), through the collection of qualitative and quantitative data during an ethnographic study in two small- to medium-sized software development companies in Jordan. Through discussion and analysis of the RE processes witnessed during the ethnographic study, the thesis answers the research question “What are the analysts’ practices in the context of packaged software implementation by small packaged software vendors?”, it provides a comparative analysis of the practices used in traditional RE and in packaged software implementation RE (PSIRE), and in doing so it also identifies novel RE practices for packaged software implementation that have not been noted in prior research. Contribution is made to the understanding of RE practices as related to packaged software implementation through the in-depth discussion of innovative RE practices and particularly through a thorough explanation of the feasibility study for PSI. The research findings lead to the provision of a Parallel Star Model depicting the practices of packaged software implementation RE at SPSVs. This Parallel Star Model demonstrates that more than one RE practice may be carried out at the same time during packaged software implementation, and provides guidance for those SPSVs about to engage in RE for packaged software implementation. This study also delivers an innovative understanding of PSIRE: first, the analyst has more of a hybrid analyst-sales-marketing role. Secondly, the use of a live scenario software demonstration in order to convince the client to buy into the PS may lead to increased perceived feasibility and reduced resistance to PS implementation. Thirdly, the assessment criteria that are used to estimate the effort and time needed for PS implementation are new features, level of customisation, software ‘output’, and technical needs. Fourthly, the Parallel Star Model shows that during PSIRE, more than one RE process can be carried out at the same time. The Parallel Star Model has few constraints, because not only can processes be carried out in parallel, but they do not always have to be followed in a particular order. This study therefore offers a novel investigation and explanation of PSIRE practices, approaching the phenomenon from the viewpoint of the analysts, and offers the first extensive study of packaged software implementation RE (PSIRE) in SPSVs
Keywords: Packaged software implementation; Requirements engineering; Small software enterprises; Ethnographic study